Free fatty acid profiles of oil derived from unripe fresh fruit bunch and its management: a case study at Sime Darby Kempas Palm Oil Mill / Normarita Saba - Saba, Normarita (Faculty of Plantation and Agrotechnology, 2017)
Palm oil is currently the major vegetable oils traded in the world. Malaysia is the second largest producer and exporter of palm oil. For hundreds of year, it forms an important ingredient in the diet of many people. The profitability of a palm oil mill is determined by its Oil Extraction Rate (OER) and the quality of the extracted oil in terms of Free Fatty Acid (FFA), moisture, impurity content, and bleach ability. In normal daily operation, about 8% of oil palm Fresh Fruit Bunches (FFB) is rejected because of unripe. Consequently the OER of the mill would be affected. Thus this study was conducted to determine the FFA profiles of unripe FFB so that satisfactory economic analysis could be performed and then some management recommendation could be made. The FFA profiles were analysed using two statistical method; One Way-analysis of variance (ANOVA) and Pearson correlation coefficient test. ANOVA results showed FFA concentration profiles in unripe FFB were significantly affected by storage time but not by bunch weight. The Pearson correlation coefficient test on FFA concentration profiles over storage time showed moderate linear relationship (r=0.64). There was no linear relationship for the different bunch weight (r=0.03). A low FFA concentration contribute to the better quality of palm oil.